Biogas production from municipal solid waste (MSW) insights into feedstock preparation and upgrading techniques - Ahmad Farid, Mohammed Abdillah; Norrrahim, Mohd Nor Faiz; Lease, Jacqueline (Springer, 2024)
This chapter comprehensively explores biogas production from municipal solid waste (MSW), revealing its intricate process. Covering crucial aspects, it enhances our grasp of renewable energy extraction from waste. Examining feedstock preparation emphasizes its role in optimizing biogas production. Identifying suitable MSW types targets efficient waste utilization, redefining waste as a resource. The various stages involved in biogas production from MSW are outlined, and process optimization strategies to enhance biogas production are discussed in detail, including the influence of types of waste, feedstock preparation, and operating conditions on biogas yield. Strategies like co-digestion and innovative reactor design boost biogas production from MSW, enhancing efficiency. Technological advancements, including physiochemical and adsorption techniques, maximize biogas yield. Biogas applications in energy and heat underscore its positive impact. The article also highlights the opportunities and potential for biogas production from MSW, explaining its significance for the wider biogas industry. Yet, challenges, from finance to tech complexities, must be recognized for effective solutions. Acknowledging hurdles paves the way for realizing biogas potential. Considering opportunities and concerns offers a comprehensive view of MSW-based biogas production’s future. This analytical work is a valuable resource for advanced researchers, policymakers, and practitioners interested in sustainable waste management and renewable energy production.